Jezik, družba in kultura - Šabec, Nada (Slavistična revija, 2006)
The author addresses Slovene-English language contact, both in the immigrant context and in Slovenia. The direct contact of Slovene and English in the case of Slovene Americans and Canadians is examined from two perspectives: social and cultural on the one hand and linguistic on the other. In the first part, I present the general linguistic situation in Cleveland (and to a minor extent in Washington, D.C. and Toronto), with emphasis on language maintenance and shift, the relationship between mother tongue preservation and ethnic awareness, and the impact of extralinguistic factors on selected aspects of the linguistic behavior of the participants in the study. I then compare the use of second person pronouns as terms of address and the use of speech acts such as compliments to determine the role of different cultural backgrounds in the speakers' linguistic choices. The linguistic part of the analysis focuses on borrowing and code switching, as well as on the influence of English on seemingly monolingual Slovene discourse, where the Slovene inflectional system in particular is being increasingly generalized, simplified and reduced, and Slovene word order is beginning to resemble that of English. Finally, the rapidly growing impact of English on Slovene in Slovenia on various linguistic levels from vocabulary to syntax and intercultural communication is discussed.
Keywords: angleščina; borowings; code switching; English; English language; intercultural communication; jezikovni stiki; language attitudes; language contacts; language meintenance; medkulturna komunikacija; Slovene; Slovene language; slovenščina; sociolinguistics; sociolingvistika; sposojanje